Photooxidatively crosslinked acellular tumor extracellular matrices as potential tumor engineering scaffolds. (15th April 2018) - Lü, Wei-Dong; Sun, Rui-Fang; Hu, Ye-Rong; Lu, Jan-Rong; Gu, Lu; Liu, Zhi-Gang; Lei, Guang-Yan; Qiang, Zhun; Cai, Lin
Graphical abstract: Abstract: Acellular tumor extracellular matrices (ECMs) have limitations when employed as three-dimensional (3D) scaffolds for tumor engineering. In this work, methylene blue-mediated photooxidation was used to crosslink acellular tumor ECMs. Photooxidative crosslinking greatly increased the stiffness of acellular tumor ECM scaffolds but barely altered the Amide III band of the secondary structure of polypeptides and proteins. MCF-7, HepG2 and A549 cells cultured on photooxidatively crosslinked acellular tumor ECM scaffolds exhibited greater cell number per scaffold, more IL-8 and VEGF secretion, and increase migration and invasion abilities than cells cultured on uncrosslinked acellular tumor ECM scaffolds. The three tumor cell lines cultured on the stiffer photooxidatively crosslinked acellular matrices acquire mesenchymal properties (mesenchymal shift) and dedifferentiated phenotypes. Furthermore, the malignant phenotypes induced in vitro when cultured on the crosslinked scaffold promoted the in vivo tumor growth of BALB/c nude mice. Finally, the dedifferentiated cancer cells, including MCF-7, HepG2 and A549 cells, were less sensitive to chemotherapeutics. Thus, photooxidatively crosslinked acellular tumor ECMs have potentials as 3D tumor engineering scaffolds for cancer research. Statement of Significance: Natural material scaffolds have been successfully used as 3D matrices to study the in vitro tumor cell growth and mimic the in vivo tumor microenvironment. Acellular tumor ECMs are developed as 3D scaffolds for tumor engineering but have limitations in terms of elastic modulus and cell spheroid formation. Here we use methylene blue-mediated photooxidation to crosslink acellular tumor ECMs and investigate the influence of photooxidative crosslinking on structural, mechanical and biological characteristics of acellular tumor ECM scaffolds. It is the first study to evaluate the feasibility of photooxidatively crosslinked acellular tumor ECMs as 3D scaffolds for cancer research and the results are encouraging. Moreover, this study provides new research areas in regard to photodynamic therapy (PDT) for Cancer.